Impact of procedural multimedia instructions for pH BRAVO testing on patient comprehension: a prospective randomized study. Issue 1 (17th July 2019) - Moore, M D; Gray, K D; Panjwani, S; Finnerty, B; Ciecerega, T; Afaneh, C; Fahey, T J; Crawford, C V; Zarnegar, R
SUMMARY: The positive impact on patient comprehension and improved procedural outcomes when multimedia is utilized to convey instructions preprocedurally has been previously shown for gastrointestinal procedures such as colonoscopy. However, in gastroesophageal reflux testing (GERD), we continue to utilize verbal and written instructions to establish this diagnosis when we use BRAVO pH testing. This is arguably a more complex procedure involving stopping medications, placement of a device, and maintaining an accurate diary for the duration of the testing. We hypothesize that by utilizing multimedia to relay complex textual information, patients will have improved comprehension of periprocedural instructions thereby improving data entry and satisfaction of expectations during the procedure. Prospective randomized study of 120 patients undergoing endoscopic placement of the BRAVO pH monitoring capsule for evaluation of GERD receive either written preoperative instructions (control) or written plus video instructions (video group). A composite comprehension score was calculated using procedure-specific parameters of data entry over the 48-hour monitoring period. Patient satisfaction was evaluated on the basis of a five-point Likert scale. Extent of patient satisfaction was defined by the fulfillment of patient expectations. Exclusion criteria included patients who did not have access to the video or did not complete follow-up. Seventy-eight patients completed all follow-up evaluations. The video group ( n = 44) had a significantly higher mean comprehension score when compared to the control group ( n = 34) (9.6 ± 1.4 vs. 7.4 ± 2.0, P = 0.01). Overall satisfaction with instructions was significantly higher in the intervention group (91% vs. 47%, p 0.01). We detected no significant difference in comprehension or satisfaction scores in subgroup analyses of the video group comparing patients <65 and ≥65 years of age and by education level. Compared to standard written instructions, video instructions improved patient comprehension based on data evaluation, and satisfaction. Therefore, clinicians should consider incorporation of multimedia instructions to enhance patient periprocedural expectations and understanding of reflux pH testing using the BRAVO procedure.